Enhancing English Speaking Skills through Learning Media and Discourse Marker Mastery: A Quasi-Experimental Study - Suryadi, Suryadi; Erlangga, Fajar (VELES Voices of English Language Education Society, 2024)
Challenges such as disinterest in learning media and poor conversation structuring skills impact English speaking proficiency among Indonesian senior high school students. This study uses a quasi-experimental design with non-equivalent control groups in a 2 x 3 factorial pre-test-post-test format to investigate how learning media and mastery of discourse markers affect speaking skills. One hundred students from a State Islamic High School in Serang participated. Data were collected through a speaking assessment and a discourse markers test, then analyzed using inferential statistics and Two-Way ANOVA. Results indicate that the effectiveness of learning media on speaking outcomes is contingent upon the student's mastery of discourse markers. Specifically, Scrabble was more effective than Flashcards at improving speaking performance for students with varying levels of discourse marker proficiency. These findings underscore teachers' need to adopt engaging English learning media and intensively teach discourse markers to enhance students' speaking abilities.